2014
DOI: 10.1073/pnas.1419030111
|View full text |Cite
|
Sign up to set email alerts
|

Antisense COOLAIR mediates the coordinated switching of chromatin states at FLC during vernalization

Abstract: Long noncoding RNAs (lncRNAs) have been proposed to play important roles in gene regulation. However, their importance in epigenetic silencing and how specificity is determined remain controversial. We have investigated the cold-induced epigenetic switching mechanism involved in the silencing of Arabidopsis thaliana FLOWERING LOCUS C (FLC), which occurs during vernalization. Antisense transcripts, collectively named COOLAIR, are induced by prolonged cold before the major accumulation of histone 3 lysine 27 tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
373
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(397 citation statements)
references
References 38 publications
12
373
1
1
Order By: Relevance
“…Natural variation studies identified multiple putative cis-elements within FLC locus that are necessary to mediate proper vernalization response (Li et al, 2014;Coustham et al, 2012). In addition, several noncoding RNAs have been reported to play roles in vernalization-mediated FLC repression (Heo and Sung, 2011;Csorba et al, 2014). Therefore, the vernalization response utilizes multiple regulatory modes to ensure that vernalization occurs in response to only prolonged cold of winter and the binding preference of VIN3-PHD finger also plays an important role in mediating proper vernalization response through monitoring the status of FLC chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Natural variation studies identified multiple putative cis-elements within FLC locus that are necessary to mediate proper vernalization response (Li et al, 2014;Coustham et al, 2012). In addition, several noncoding RNAs have been reported to play roles in vernalization-mediated FLC repression (Heo and Sung, 2011;Csorba et al, 2014). Therefore, the vernalization response utilizes multiple regulatory modes to ensure that vernalization occurs in response to only prolonged cold of winter and the binding preference of VIN3-PHD finger also plays an important role in mediating proper vernalization response through monitoring the status of FLC chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The vernalization process (prolonged cold exposure) is essential for many plants to initiate flowering. In Arabidopsis and other crucifers, this process is mediated by coldinduced epigenetic repression of FLC genes, namely, histone methylation (Bastow et al, 2004), chromatin structure modification with chromatin remodeling protein complexes (Kim and Sung, 2013), and the expression of long noncoding RNAs (Csorba et al, 2014). Genes flanking FLC are epigenetically coordinately regulated (Finnegan et al, 2004).…”
Section: Lineage-specific Genomic Context Of Mads-box Genes: Potentiamentioning
confidence: 99%
“…Both of these involve accumulation of high levels of H3K27me3 at FLC (20)(21)(22). A series of FLC antisense transcripts (COOLAIR) contribute to these repression pathways (18,(23)(24)(25)(26). Our previous work revealed that H3K36me3 is associated with an actively transcribed FLC ON state, opposing an H3K27me3 OFF state, where a high level of H3K27me3 across FLC maintains long-term silencing (18,23).…”
mentioning
confidence: 98%
“…Both of these involve accumulation of high levels of H3K27me3 at FLC (20-22). A series of FLC antisense transcripts (COOLAIR) contribute to these repression pathways (18,(23)(24)(25)(26) Opposing H3K36me3 and H3K27me3 states are particularly interesting as previous theoretical analysis had predicted the existence of such opposing, mutually exclusive histone modification states (23,28). Such a system would be maintained by nonlinear positive feedback mechanisms that could give robust bistability, resistant to noise and DNA replication.…”
mentioning
confidence: 99%